La science politique en Amérique latine : une discipline pluridisciplinaire - Daniel Buquet (Revue d’Histoire des Sciences Humaines)
In Latin America, political science was historically constituted from the confluence of different disciplines: philosophy, history, law, and sociology. However, it remained subsumed until very recently, and only began to clearly differentiate itself after the third wave of democratization in the 1980s. This article traces the main moments of Latin American political science in the light of the evolution of its institutional situation, particularly in university and academic structures, but also concerning the shifts in its centers of interest, the intellectual orientations that have prevailed within it, and the debates that have crossed it.